4x-13=-23-2x

Simple and best practice solution for 4x-13=-23-2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x-13=-23-2x equation:


Simplifying
4x + -13 = -23 + -2x

Reorder the terms:
-13 + 4x = -23 + -2x

Solving
-13 + 4x = -23 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
-13 + 4x + 2x = -23 + -2x + 2x

Combine like terms: 4x + 2x = 6x
-13 + 6x = -23 + -2x + 2x

Combine like terms: -2x + 2x = 0
-13 + 6x = -23 + 0
-13 + 6x = -23

Add '13' to each side of the equation.
-13 + 13 + 6x = -23 + 13

Combine like terms: -13 + 13 = 0
0 + 6x = -23 + 13
6x = -23 + 13

Combine like terms: -23 + 13 = -10
6x = -10

Divide each side by '6'.
x = -1.666666667

Simplifying
x = -1.666666667

See similar equations:

| 6.5x=x^2-10 | | 6.5x/x^2 | | m^4+16m^3+96m^2+256m+256=0 | | 8[2-8(-4x-1)]=256x+80 | | (6x^10y)/(2x^4y) | | e^3x-9=7 | | 3m-4=-4-4m-m | | 0.6x+19.3=x-2.18 | | 2x+x+x-50=15000 | | 4x+7.6x=2(3x-3.2) | | -24=-40q | | -0.2x+3.93=-0.4x+1.93 | | 2x+x+(x-50)=15000 | | A*50=x | | 2x+x(x-50)=15000 | | 300x-.14=500x+.34 | | 2.6x-70=1.3x+8 | | 1y-9=14 | | 2.6x-70=13x+8 | | x^2-5*x+2.7=0 | | 1+r=-7 | | 16a-2x(2+4b)+5b= | | 1,5x+4=30+x | | 8x-36=10x-40 | | -y+225=58 | | 120-v=280 | | 192=-x+93 | | -7d-3+3d-4d-4d=-3 | | cot^2(x)=.33 | | 8x7/9 | | 16x+8=30-12x+8 | | 5cos^2(x)=4 |

Equations solver categories